Best Jewish books for Children and Teens : A JPS Guide - Silver, Linda R. (Book collections on Project MUSE., 2010)
Linda Silver selected the titles that "represent the best in writing, illustration, reader appeal, and authentically Jewish content--in picture books, fiction and non-fiction, for readers ranging from early childhood through the high school years."--P. 4 of cover.